수중 부유물질의 임계 표면 장력에 따른 부유 선별 처리 특성에 관한 기초 연구 - 한신혜; 김동수 (한국수처리학회지, 28(2), 2020)
Flotation has been used to separate suspended solids from aqueous environments in that it requires low installation cost and little space to perform an action, and can be automated easily. The surface features of the suspended solids have a large influence on the performance of flotation, and it is important to probe the relationship between surface features and their floating behavior in order to perform flotation effectively, which is the purpose of this research. In this work, the contact angle of subjects in the form of a sessile drop was measured to derive a Zisman plot and critical surface tension. The samples which are expected to be prevalent in aqueous systems were collected and divided into three different categories. The organic compounds including plastics (polyethylene terephthalate, polypropylene, high-density polyethylene, low-density polyethylene, polyvinyl carbonate, and polystyrene) showed high critical surface tension, and it was therefore concluded that they could be easily separated from water using the flotation method. On the contrary, the inorganic compounds such as metals (stainless steel and aluminum) and minerals (glass and pyrite) were determined to be hydrophilic, which suggested the necessity to perform a pre-treatment on these compounds to adjust the hydrophilicity of the materials. In conclusion, this research was performed to determine the colloidal state of particles and the expected risks when these particles are dispersed in aqueous environments in terms of the critical surface tension. These findings could provide a basis for further research to enhance the flotation process by determining a way to collect samples in the same conditions such as roughness, flatness, and production method. KCI Citation Count: 0